Warisan Kriya Tekstil Aceh: Kajian Terhadap Tenun Songket Dan Sulam Kasab - Rahmawati; Niko Andeska; Miftahun Naufa (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Acehnese textile crafts represent an essential form of local wisdom that warrants in-depth study to understand their developmental dynamics in the contemporary era, with a specific focus on two primary objects tenun songket and sulam kasab. This study aims to explore the historical aspects, production techniques, symbolic motifs, as well as the functional and cultural values embodied in these crafts. Employing a qualitative interpretative approach, the research is based on a systematic literature review complemented by contextual analysis derived from field observations and interviews with artisans and cultural experts. The findings reveal that Acehnese textile crafts, particularly tenun songket and sulam kasab, possess not only aesthetic and spiritual values but also function as cultural texts that reflect Islamic philosophy and the collective identity of Acehnese society. Historically, these crafts evolved through cultural acculturation during the Aceh Sultanate period, while symbolic motifs such as Pinto Aceh and Bungong Meurante represent humility, unity, and piety. In terms of sustainability, the study identifies several adaptive strategies, including the regeneration of female artisans, the application of eco-friendly natural dyeing techniques, and the integration of community-based creative economies through education and digital marketing. These findings highlight the importance of innovation grounded in local wisdom to sustain the heritage of Acehnese textile crafts and enhance their relevance within both cultural and global economic contexts.